Reelin molecules assemble together to form a large protein complex, which is inhibited by the function-blocking CR-50 antibody - Utsunomiya-Tate, Naoko (The National Academy of Sciences, 2000)
Reelin is a key mediator of ordered neuronal alignment in the brain. Here, we demonstrate that Reelin molecules assemble with each other to form a huge protein complex both in vitro and in vivo. The Reelin–Reelin interaction clearly is inhibited by the function-blocking anti-Reelin antibody, CR-50, at a concentration known to inhibit Reelin function. This assembly is mediated by electrostatic interaction of the CR-50 epitope region. Recombinant CR-50 epitope fragments spontaneously constitute a soluble, string-like homopolymer with a regularly repeated structure composed of more than 40 monomers. Mutated Reelin, which lacks the CR-50 epitope region, cannot form a homopolymer and fails to induce efficient tyrosine phosphorylation of Disabled 1 (Dab1), which should occur to transduce the Reelin signal. These data suggest that Reelin exerts its biological function by composing a large protein assembly driven by the CR-50 epitope region, proposing a novel model of the Reelin signaling in neurodevelopment.